Catalytic degradation of melamine–formaldehyde resins into valuable chemicals. Issue 19 (22nd September 2021) - Wu, Shaodi; Zhang, Ning; Jia, Shiyu; Wang, Chizhou; Wang, Yingxiong; Qi, Yongqin; Wang, Hongliang; Cui, Xiaojing; Hou, Xianglin; Deng, Tiansheng
Abstract : Catalytic degradation of waste melamine–formaldehyde resins into chemicals via the selective cleavage of specific C–N bonds under mild conditions. Abstract : The wide application of melamine–formaldehyde resins (MFRs) in the food industry aggravates plastic pollution problems. Recycling of the waste MFRs remains a big challenge due to its compact structure. Herein, a high MFR degradation ratio of ca. 84 wt% was achieved under mild conditions (180 °C) in a methanesulfonic acid (MSA)–tetrahydrofuran (THF)–H2 O system with cyanuric acid as the main degradation product. The SEM results showed that the degradation of MFRs followed different reaction mechanisms when H2 O and THF were applied as solvents, respectively. The combination of the two solvents showed an obvious synergistic effect for the degradation of MFRs. The degradation experimental results with melamine as the model intermediate indicated that the degradation of MFRs proceeded via the selective cleavage of the sp 2 C–sp 3 N and sp 3 C–sp 3 N bonds to recover valuable C and N alternated-aromatic ring (CNAR) units, followed by their transformation into a valuable chemical of cyanuric acid.